2005
DOI: 10.1177/0731684405043552
|View full text |Cite
|
Sign up to set email alerts
|

Study of SiO2 Nanoparticles on the Improved Performance of Epoxy and Fiber Composites

Abstract: SiO2-epoxy and SiO2-glass-fiber epoxy nanocomposites were prepared to study the influence of SiO2 nanofiller particles on the mechanical properties. The size and concentration of free volume were tested by positron annihilation spectroscopy. The experimental results demonstrate that uniform dispersion of nanoparticles play an important role in promoting the comprehensive performance of nanocomposites. 115, 13, and 60% increase have been achieved at 3 wt% of nanoparticles for the tensile strength, tensile modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 20 publications
4
48
0
1
Order By: Relevance
“…Mechanical mixing of Araldite LY564 and silica powder was carried out using a mechanical stirrer at 600 rpm for 30 min. Then the hardener was mixed 8 mechanically into the epoxy and the mixture was left to cure at room temperature for 3 days.…”
Section: Solvent-free Dispersion Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical mixing of Araldite LY564 and silica powder was carried out using a mechanical stirrer at 600 rpm for 30 min. Then the hardener was mixed 8 mechanically into the epoxy and the mixture was left to cure at room temperature for 3 days.…”
Section: Solvent-free Dispersion Techniquesmentioning
confidence: 99%
“…Nanocomposites with silica nanoparticles have been reported to display increased mechanical properties [8,9] such as modulus, tensile, flexural and impact strength up to a certain silica content (e.g. 2.5% [10]) and decreased mechanical properties thereafter, improved fracture toughness [11] and better thermal stability [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…5%) 13 and decreased mechanical properties thereafter, improved fracture toughness 14 and better thermal stability. 15,16 Hybrid composites including fibre reinforcement in a polymer matrix with dispersed nanoparticles have been the subject of several recent studies where it has been reported that the nanoparticle-fibre composites, when compared with the corresponding fibre composites, displayed higher in plane shear strength (glass fibreorganoclay-epoxy composites 17 ), increased interlaminar shear strength, flexural strength, flexural modulus and fracture toughness (glass fibre-clay-vinyl ester composites, 5 glass fibre-clay-epoxy composites, 18 carbon fibre-clay-epoxy composites, 19 glass fibre-silica-epoxy composites 11 ) and better thermal properties. 5,18 However, there are no studies on the processability of such composites, especially at relatively high fibre content.…”
Section: Introductionmentioning
confidence: 94%
“…One method to create silica particles, which was developed by Stöber more than 30 years ago, uses the sol‐gel process [10]. In the Stöber process, silica particles are created by the hydrolysis and condensation of silicon alkoxides in alcohol solvents in the presence of a base (e.g., NH 3 ) and H 2 O. Silica nanoparticles dispersed homogeneously within polymer matrices, for example, have been reported to enhance mechanical properties [11, 12] including Young's modulus, flexural, tensile, and impact strength. As a result, fracture toughness [13] and thermal stability [14, 15] are also improved.…”
Section: Introductionmentioning
confidence: 99%